Levitating trains and kamikaze genes : - Brennan, Richard P. (Wiley, 1990)
As our world becomes increasingly more technological, some of us are getting left behind. Here is a quick and easy course in the terms and concepts of science to help the reader understand the technology of our modern world. Includes a technological literacy test. 49 line drawings.